Determinants of country-level employee overqualification - Nikolovski, Aleksandar (Economic and business review, 2022)
We build on the configurational approach to identify patterns of macro contextual factors leading to high country-level employee overqualification. We differentiate between subjective and objective employee overqualification and establish that each is caused by different configurations of macro factors. We also identify country-level overqualification arechetypes and link specific countries with respective archetypes. We find that a country’s non-vocational education system is a necessary condition for high objective overqualification, while objective overqualification itself is not a necessary condition for perceived overqualification. We discuss theoretical implications and offer policy implications.
Keywords: employment; enterprises; kvalifikacija; podjetje; qualification; zaposlovanje